Customer Satisfaction Based on Kano & Quality Management Model: A Bibliometric Analysis of Global Publications - Widodo, Rochmad Agung; Suef, Mokh; Affandi, Achmad (Journal of Posthumanism, 2025)
The study reveals a direct and significant relationship between economic impact and tourism reactivation in wholesale travel agencies in Peru. It highlights the importance of economic growth strategies for the revival of tourism. In addition, a moderate relationship is identified between social impact and tourism reactivation, highlighting the importance of promoting a positive social impact. A significant correlation is observed between sustainable development practices and tourism recovery, highlighting the importance of an effective organizational culture. This original correlational design study evaluates the relationship between sustainable development and tourism recovery in travel agencies in Peru. It implies that sustainable practices and a focus on economic and social impact are crucial for agency success and sustainable tourism growth. Further research on specific sustainable development strategies and cultural factors is suggested for future research. This study analyzes global publication trends related to customer satisfaction using the Kano model and quality management frameworks through bibliometric analysis. The use of the Kano model in measuring customer satisfaction has gained importance across various sectors, yet no comprehensive study has explored the evolution of research in this field. Therefore, this study uses the Scopus database to analyze 244 articles published between 1994 and 2025. Methods such as citation analysis and co-occurrence analysis are employed to identify key themes, authors, countries, and emerging research trends. The findings reveal a significant increase in publications since 2010, with a focus on three main thematic clusters: 1) Kano Model & Customer Insights, 2) Quality Management and Decision-Making Tools, and 3) Product Development and Customer-Centric Design. Countries such as China, Taiwan, and the United States emerge as major contributors. The study also identifies potential future research directions, including integrating the Kano model with emerging technologies like AI and IoT, as well as exploring cross-cultural studies and social responsibility in customer satisfaction. The implications suggest that while research in this area has advanced, there is still considerable room for further exploration, especially in practical applications and the integration of new technologies to enhance real-time customer satisfaction analysis.